The Research And Development Performance Of Various EU Social Regimes - Puškárová, Paula; Gurníková, Jana (Comparative Economic Research. Central and Eastern Europe, 2014)
The paper provides a new approach to the classification of EU countries into innovation-performance groups, taking into account their social regime. In the Introduction, it draws on some empirical evidence of synchronised research and development (R&D) performance within a social regime. In the second and third parts it reviews the literature on measuring R&D performance, and in the fourth part it summarizes social regime classifications. The fifth and longest part of the paper proceeds to a comparative analysis of the empirical data, pointing out disparities, both respects to numbers and members, in the composition of innovation-performance groups. In the final part, the paper summarizes key findings.